Comparison of traps and formulations of grandlure for catching the boll weevil - Melo, Alexandre Brito Pereira de; Silveira Neto, Sinval; Carvalho, Ricardo Pereira Lima (Pesquisa Agropecuaria Brasileira, 2014)
Different types of traps and formulations of grandlure were compared for catching the Anthonomus grandis (Boh., 1843). This research was conducted in two periods. The first, from 28.5.83 until 17.8.83 when the cotton plants were 130 days old; the second one from 3.10.83 to 9.11.83, after 40 days of planting. In both periods IAC/EMBRAPA trap was the most efficient in catching the insects. Hardee and Hercon traps were less efficient and there were no statistical difference between them. There was no correlation between traps and formulations of pheromone. However, the majority of adults were catched when it was used the grandlure formulation "Sanduíche" type for all the periods and traps used.